INNOVATIVE TECHNOLOGIES IN OIL INDUSTRY: INTELLECTUAL EQUIPMENT OF WELLS - R. S. Sadykova; L. A. Abdullina; L. I. Gazizullina (Russian Journal of Economics and Law)
RETRACTION:The article published in the scientific Journal “Actual Problems of Economics and Law” (2013. No. 2. Pp. 94–100) under the title “Innovative technologies in oil industry: intellectual equipment of wells” under the authorship of R. Sh. Sadykova, L. A. Abdullina, L. I. Gazizullina is withdrawn by an editor with the consent of the publisher and the author.Retraction is due to incorrect borrowing from:1. Aver'yanov D. A. Intellektual'nye sistemy v neftegazovom dele // Neft'. Gaz. Novatsii. 2011. № 11. S. 24–26https://elibrary.ru/item.asp?id=176822652. Eremenko O. V. Effektivnost' razvitiya resursnogo potentsiala neftegazodobyvayushchego predpriyatiya innovatsionnym metodom intellektual'nykh skvazhinnykh sistem // Intellekt. Innovatsii. Investitsii. 2012. № 2. S. 24–27https://www.elibrary.ru/item.asp?id=18641378